(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
HISTORY OF THE POSTAL SERVICES IN CRACOW The post as a symbol of communication has been with the humanity for many centuries already. As it enabled contact and helped circulate information, it contributed much to the development of civilization. Cracow has the most eventful history of the post of among all the cities in Poland. In 1846 Austria abolished the Free City of Cracow. After annexation, the occupying authorities set to adapting the postal system in Cracow to the Austrian system. A year later the first train left Cracow, which began the era of railway transport. The Cracow postal services faced the problem of reorganizing and adjusting the postal dispatch system to the requirements of rail transport. Cracow was the first city in the Austrian Empire to which a postal lorry was directed from Vienna, therefore numbered 1. In 1850 postal stamps appeared here for the first time. The development of Cracow required the opening of new post offices in the city and neighbouring communities and suburban settlements, which where then successively incorporated into the city proper. The main goal of this study is to give the most exhaustive information possible about those post offices. In 1918 Cracow was one of the first cities worldwide to have regular airmail connection with other places. The activity of the Cracow Post during the First World War is especially well documented thanks to its involment in services to Polish military units fighting for independence; first to the Riflemen and later to the Polish Legions. The variety of forms of these activities enriches our knowledge of military events at that time, and justifies the thesis that the history of the Post is determined by the history of our city.